Saudi Arabia-Qatar. From Cooperation to Confrontation - Pashayan, Araks (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
On June 5, 2017, the Kingdom of Saudi Arabia (KSA) and its allies subjected Qatar to a series of boycotts and blockades. The initiative came from KSA, which was concerned over Qatar’s growing ambitions to become an influential state in the region. In these terms, the launch of the blockade was intended to diminish Qatar’s political autonomy and economic independence. Qatar never saw its tiny population and territory as a barrier to an independent foreign policy or regional infl uence.
Keywords: Political science